Wounded citizenship: the post-colonial city and poor whites. Issue 1 (2nd January 2018) - Sibanda, Octavia
Abstract : This paper focuses on wounds inflicted on poor whites in South Africa by the post-colonial city emanating from a changing socio-political and economic landscape. Contrary to the general assumption that the modern city project "historically embraced whites and continues to do so, " I argue that poor whites have been bruised and wounded by the post-colonial city. I make a case that neo-liberalism as well as political changes have presented poor whites with something new and unpleasant, thereby leading to experiences of rejection, shame and uncertainty. The paradox of these experiences is that, while poor whites bear the historical shame of being part of the initial "wounders, " they also carry the identity of the "wounded" in contemporary South Africa. However, white poverty and white dispossession are often trivialised in the South African context, thereby making it "invisible." In this paper, I highlight how poor whites carry a "wounded citizenship" in post-apartheid South Africa.